سحب المشروع من المقاول في عقود الأشغال العامة (دراسة مقارنة) - صنية خمري; ليدية بن جديد (My University, 2017)
Summary: From our previous study, it has become clear to us that the penalty for withdrawing work from the contractor is an important topic, being a compelling sanction. It serves as a concession granted to the contracting stakeholder in order to compel the breached contractor to perform and fulfil its agreed contractual obligations in accordance with the terms and conditions of the contract concluded, Where the contracting interest replaces it, or entrusts it to another measure in order to remedy its errors, At its expense and under its responsibility, it is a temporary measure that does not terminate the contractual relationship, It remains with the original contractor, and by reference to article 35 of the Algerian General Administrative Conditions Book, Algerian legislation does not deal with the penalty for withdrawal of work in an integrated manner. Where in the event of a flawed execution, the employer is given the path of a direct system, which may be partial or total as the case may be ............................. ملخص : اتضح لنا من خلال دراستنا السابقة، أن جزاء سحب العمل من المقاول من المواضيع الهامة، كونه من الجزاءات الضاغطة. إذ يعد بمثابة امتياز من الامتيازات الممنوحة لجهة المصلحة المتعاقدة، من اجل إجبار المتعاقد المخل على تنفيذ و الوفاء بالتزاماته التعاقدية المتفق عليها وفق بنود و شروط العقد المبرم، حيــث تـحــل المصلحة المتعاقدة محله، أو تعهد بـه إلـى مقـاول أخـر مــن اجـل إصلاح الأخطاء التي ارتكبها ، و تكون على حسابه و تحـت مسؤوليتــــــــه، و هـو إجـــــــراء مؤقت لا ينهي العلاقة التعاقدية، و إنما تبقى قائمــة مـع المتعاقد الأصلي، و بالرجوع إلى المادة 35 من دفتر الشروط الإدارية العامة الجزائري نجد ان المشرع الجزائري لم يتناول جزاء سحب العمل بصورة متكاملة، حيـث أعطى لصاحب العمل في حالة التنفيذ المعيب أن ينتهج طريق النظام المباشر و الذي يجوز أن يكون جزئيا أو كليا بحسب الأحوال . ............................ Résumé : D’après notre étude précédente, il est devenu clair pour nous que la pénalité pour le retrait des travaux de l’entrepreneur est un sujet important, étant une sanction convaincante. Il sert de concession accordée à l’acteur contractuel afin d’obliger l’entrepreneur violé à exécuter et à remplir ses obligations contractuelles convenues conformément aux termes et conditions du contrat conclu, Lorsque l’intérêt contractuel le remplace, ou lui confie une autre mesure afin de remédier à ses erreurs, À ses frais et sous sa responsabilité, il s’agit d’une mesure temporaire qui ne met pas fin à la relation contractuelle, Il reste avec l’entrepreneur d’origine, et par référence à l’article 35 du Cahier général des conditions administratives algériennes, la législation algérienne ne traite pas de la sanction pour le retrait du travail de manière intégrée. Lorsque, en cas d’exécution fautive, l’employeur se voit donner la voie d’un système direct, qui peut être partiel ou total selon le cas.